2006
DOI: 10.1021/nl061294a
|View full text |Cite
|
Sign up to set email alerts
|

Contact Formation Dynamics:  Mapping Chemical Bond Formation between a Molecule and a Metallic Probe

Abstract: We present a study that maps out chemical bond formation between a Pt-inked probe and a single 1,3-cyclohexadiene (1,3-CHD) molecule on Si(100). By separating the mechanical and electronic contributions to the current during the approach to contact, we show that there are significant forces between the probe and the CdC of the molecule and we track the relaxation of the molecule, the emergence of a chemical bond feature in the LDOS, and the quenching of specific molecular vibrations during bond formation.Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…4(b). In particular the 2 level at 0:2 eV agrees well with the 0:35 eV feature in the LDOS reported previously at small probe-molecule separations [16].…”
supporting
confidence: 90%
See 3 more Smart Citations
“…4(b). In particular the 2 level at 0:2 eV agrees well with the 0:35 eV feature in the LDOS reported previously at small probe-molecule separations [16].…”
supporting
confidence: 90%
“…In contrast to metal systems where the interaction increases the apparent corrugation, here a new state is created close to the Fermi energy (E f ) that dominates transport into the molecule-surface system. These data demonstrate that wide band-gap low-conductance molecules such as 1,3-CHD may form electrically active interface states with metals and that STM can be used to explore contact formation and to screen molecules for potential electronic applications.Previously, we showed that STM can distinguish between the reaction products of 1,3-CHD on Si(100) [13,14] and directly measures the force of the probemolecule interaction [15], including the onset of local density of states (LDOS) feature that was attributed to incipient chemical bond formation [16]. Figures 1(a)-1(e) show empty-state STM images of the five different 1,3-CHD attachment geometries in which the single remaining C --C bond appears to be the origin of the contrast FIG.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1(b)], which is known to be associated with the C --C bond region of the 1,3-CHD molecule in the intradimer [2 2] configuration [15], and the approach experiment was repeated at a sample bias of 200 meV. The low bias was chosen because within the corresponding tunneling energy window the local density of states (LDOS) was measured to be independent of the probe-molecule separation [16]. Experimentally, the approach involved applying a 0.01 nm dither at 534 Hz to the Z piezo under openloop conditions so that the current and the first and second harmonics (dI=dZ and d 2 I=dZ 2 ) are measured simultaneously using a dual-phase lock-in amplifier (SR/7265), and shown in Figs.…”
mentioning
confidence: 99%